Composition for packaging and use method and application thereof
By using compositions of fluoroaryl compounds, ultraviolet curable monomers, additives and photocrosslinking initiators in the packaging materials, the problems of high dielectric coefficient, poor light transmittance and poor mechanical properties of existing packaging materials are solved, and the packaging film with low dielectric constant, high light transmittance and excellent mechanical properties are achieved, which improves the performance and reliability of electronic devices.
Patent Information
- Application Number
- CN202411983056.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-22
AI Technical Summary
The high dielectric coefficient, poor light transmittance and poor mechanical properties of existing packaging materials lead to lower signal transmission quality and efficiency of electronic devices in high-frequency applications, reduced luminous efficiency, and prone to problems such as film cracking and peeling under the action of external forces.
Using a packaging composition, which includes a fluoroaryl compound, an ultraviolet curable monomer, an additive and a photocrosslinking initiator, the packaging film with low dielectric constant, good light transmittance and excellent mechanical properties is formed by adjusting the ratio.
It realizes the reduction of the dielectric properties of the packaging materials, improves the light transmittance and mechanical properties, enhances the heat resistance and flexibility of the packaging film, and extends the service life of electronic devices.
Smart Images

Figure BDA0005221954380000021 
Figure BDA0005221954380000031 
Figure BDA0005221954380000032
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of organic thin film packaging materials, and specifically relates to a packaging composition and a use method and application thereof. Background Art
[0002] In the field of electronic device packaging, the performance of packaging materials has a crucial impact on the reliability, stability and service life of electronic devices. With the continuous development of electronic technology, the requirements for packaging materials are becoming increasingly stringent.
[0003] There are many problems with the cured packaging film formed by UV curing of traditional packaging materials. For example, China's public patent CN115109464B discloses an ink composition, including a photocurable silicon-containing monomer component, a reactive diluent component and a photoinitiator component. The fluorine-substituted silicon-containing monomer is used in combination with the reactive diluent component to reduce the dielectric constant. The dielectric constant is generally high (greater than 2.7). Under the action of the electric field, the high dielectric constant will lead to uneven electric field distribution inside the material, increase power loss, and affect the signal transmission quality and efficiency of electronic devices. This problem is particularly prominent in the application of high-frequency electronic devices. At the same time, this type of packaging film has poor light transmittance. For some electronic devices that require light transmission, such as organic light-emitting diodes, poor light transmittance will reduce the luminous efficiency and display effect of the device. Furthermore, its mechanical properties are poor, manifested in insufficient tensile strength, low elongation at break, and poor bending resistance. When the electronic device is subjected to external forces or thermal expansion and contraction during use, the film layer is prone to cracking and peeling, thereby destroying the integrity of the packaging structure and causing the electronic device to fail or perform poorly.
[0004] The above defects of existing packaging materials seriously restrict the further development of electronic devices in the direction of high performance and high reliability. Therefore, it is urgent to develop a packaging composition to overcome the above problems to meet the strict requirements of modern electronic device packaging.
[0005] In view of this, this invention is proposed. Summary of the invention
[0006] The purpose of the present invention is to overcome the shortcomings of the above-mentioned prior art and provide a packaging composition and its use method and application, which are mainly used to solve the problems of high dielectric constant, poor light transmittance and poor mechanical properties of the cured packaging film formed by ultraviolet light curing of the existing packaging materials.
[0007] In order to achieve the above object, the present invention adopts the following technical solutions:
[0008] In a first aspect, the present invention provides an encapsulation composition, which includes the following raw materials in parts by weight: 5 to 50 parts of a fluorinated aromatic compound, 10 to 70 parts of an ultraviolet light-curable monomer, 5 to 25 parts of an auxiliary agent, and 2 to 4 parts of a photocrosslinking initiator.
[0009] Preferably, the encapsulation composition has a formula of: 20 to 35 parts of a fluorinated aromatic compound, 30 to 65 parts of an ultraviolet light-curable monomer, 5 to 25 parts of an auxiliary agent, and 2 to 3 parts of a photocrosslinking initiator.
[0010] Furthermore, the structure of the fluorinated aromatic compound is shown in the following general formula (1):
[0011]
[0012] Wherein, PAHs in the general formula (1) represents polycyclic aromatic hydrocarbons, which refers to substituted or unsubstituted aromatic hydrocarbons containing two or more benzene rings, and at least one group on each aromatic hydrocarbon is substituted by L or Z; the L and Z are each independently selected from any one of H, F, CFH2, CF2H, CF3, C1-C12 fatty chain alkyl, C1-C12 fluoroalkyl and the groups shown in the following general formula (2), and at least one group among L and Z is a fluorine-containing group, and the fluorine-containing group is any one of F, CFH2, CF2H, CF3, C1-C12 fluoroalkyl and the groups shown in the following general formula (2);
[0013]
[0014] In the general formula (1) and the general formula (2), X is independently selected from one of F and CF3, Y is selected from one of -ORO- and -NHRO-, and R in the -ORO- or -NHRO- is selected from one of C0-C12 substituted or unsubstituted aliphatic chain alkyl, C3-C6 substituted or unsubstituted aliphatic cycloalkyl, and C6-C30 substituted or unsubstituted aryl.
[0015] The polycyclic aromatic hydrocarbons used in the present invention mainly have two combinations, one is a non-condensed ring type, including any one of biphenyl, biphenyl and polyphenylated aliphatic hydrocarbons; the other is a condensed ring type, that is, two carbon atoms are shared by two benzene rings, including but not limited to one of benzene, naphthalene, phenanthrene, anthracene, and pyrene.
[0016] Furthermore, the structure of the fluorinated aromatic compound includes at least one of the following formulas (1) to (10):
[0017]
[0018] Furthermore, the fluoroaryl compound is prepared by the following method, which is carried out in two steps under the protection of inert gas. First, the fluoroacrylic acid raw material, the acyl chloride raw material, the solvent and the catalyst are uniformly mixed according to the set ratio, and a fluoroacrylic acid chloride product is obtained after the reaction; then, the fluoroacrylic acid chloride product obtained above is added dropwise to a solution formed by an alcohol or phenol raw material containing fluorine atoms and an organic base, and the target product is obtained after reaction and post-treatment.
[0019] Furthermore, the molar ratio of the fluoroacrylic acid raw material to the acyl chloride raw material is 1:(2-4);
[0020] The molar ratio of the alcohol or phenol raw material containing fluorine atoms to the fluoroacryloyl chloride product is 1:
[0021] (2~4).
[0022] The fluoroacrylic acid raw material includes trifluoromethylacrylic acid or 2-fluoroacrylic acid;
[0023] The acyl chloride raw material includes oxalyl chloride;
[0024] The alcohol or phenol raw material containing fluorine atoms includes (R)-1-(3,5-bis(trifluoromethyl)phenyl)ethanol, 5-fluoronaphthalene-1-ol or perfluorobenzene-1-ol;
[0025] The solvent includes anhydrous dichloromethane or anhydrous ethyl acetate;
[0026] The catalyst includes N,N-dimethylformamide.
[0027] Furthermore, in the first step of preparing fluoroacryloyl chloride products, the reaction time at room temperature is 3h to 8h; in the second step, when the fluoroaryl compound is added dropwise to the solution, it should be carried out under low temperature (about 0°C), and after the reaction is completed, the solution is neutralized with dilute hydrochloric acid; then, the aqueous phase is washed with a saturated sodium bicarbonate solution; then the organic phase is removed, and the aqueous phase is extracted with ethyl acetate; thereafter, the organic solutions are combined and distilled for the first time to reduce the volume; the remaining material is purified by silica gel column chromatography, and the purified product is distilled again to obtain the target product.
[0028] It should be noted that the fluorinated aromatic compound prepared by the present invention has unique structural characteristics, with more fluorinated groups and specific phenyl structures. The introduction of fluorinated groups can effectively reduce the polarizability of the molecule. Under the action of the electric field, the degree of molecular polarization is closely related to the induced dipole moment generated. When the degree of molecular polarization is lower, the induced dipole moment generated is smaller, thereby reducing the dielectric properties of the material. In addition, the special chemical structure of the fluorinated aromatic compound has a unique influence in the encapsulation ink system. In general organic materials, strong intermolecular interactions will lead to a closer arrangement of molecules, thereby increasing dielectric properties; however, the presence of this new compound will interfere with the close arrangement of other molecules in the ink, increase the gaps between molecules, reduce the intermolecular interactions, and thus reduce the dielectric constant of the material.
[0029] In addition, the fluoroaryl compound in the present invention contains an acrylate structure, and this special structure gives it certain non-polar characteristics. When a substance containing the compound is added to the packaging ink, the overall polarity of the ink can be changed, making it closer to a non-polar state, and the dielectric properties of the packaging ink can be effectively reduced. This characteristic makes the fluoroaryl compound have important application value in the field of packaging inks, and provides an effective solution for achieving packaging inks with low dielectric properties.
[0030] Furthermore, the UV-curable monomer is a mixture of a (meth)acrylate containing a long carbon chain and a bridge-ring photocurable monomer, and the mass ratio of the UV-curable monomer to the (meth)acrylate containing a long carbon chain and the bridge-ring photocurable monomer is (20-45): (10-30).
[0031] Specifically, the (meth)acrylate containing a long carbon chain includes one or more of 1,6-hexanediol diacrylate, 2-methyl-2-acrylate-1,10-decanediol, 2-methyl-2-acrylate-1,9-nonanediol dimethacrylate, 1,5-pentanediol dimethacrylate, 1,11-undecanediol dimethacrylate, 1,12-dodecanediol di(meth)acrylate, 1,13-tridecanediol dimethacrylate, 1,14-tetradecanediol di(meth)acrylate, and 1,18-octadecanediol dimethacrylate.
[0032] The bridged ring photocurable monomers include but are not limited to bridged ring diacrylate monomers containing six to twenty-five carbon atoms, specifically one or more of dicyclopentenyl acrylate, isobornyl acrylate, cyclohexyl methacrylate, isobornyl methacrylate, dicyclopentyl methacrylate, tricyclodecane dimethanol diacrylate, tricyclodecane dimethanol dimethacrylate, dicyclopentenyl ethoxylated acrylate, dicyclopentenyl ethoxylated methacrylate, isobornyl (meth)acrylate, and dicyclopentenyl (meth)acrylate.
[0033] The glass transition temperature (Tg) of the bridged ring photocurable monomer is generally 70°C to 180°C, but in the present invention, it is preferably greater than 90°C to increase the overall Tg of the system.
[0034] It should be noted that the present invention uses (meth) acrylates containing long carbon chains, which has the advantage of ensuring the flexibility of the encapsulation composition (ink) molecule. On this basis, the addition of bridge ring photocurable monomers greatly improves the molecular rigidity. The bridge ring photocurable monomers have a relatively rigid bridge ring structure and two acrylate reaction sites, which can react with the acrylic acid group of the fluorinated aryl compound during polymerization, thereby promoting the formation of a cross-linked network structure. The formation of this cross-linked network structure significantly increases the cross-linking density, which greatly improves the heat resistance. At the same time, the selection of high Tg (greater than 90°C) bridge ring photocurable monomers effectively avoids the phenomenon that the ink is too soft and cannot be used normally due to the addition of too much (meth) acrylate containing long carbon chains. The addition of bridge ring photocurable monomers can increase the Tg of the system, so that the thermal stability of the cured ink is improved. In addition, the fluorinated aryl compound cooperates with the bridge ring photocurable monomer to effectively reduce the dielectric constant and dielectric loss, and improve the light transmittance of the cured film.
[0035] Furthermore, the auxiliary agent contains at least two maleic anhydride structures.
[0036] The present invention uses an auxiliary agent containing at least two maleic anhydride structures, by improving the compatibility and intermolecular force of each component, thereby improving the mechanical properties of the fluorine-containing low-dielectric inkjet printing material, this is because the double bonds in the maleic anhydride molecule can be polymerized with other molecules in the ink to form a more stable cross-linked structure, and this cross-linked structure can improve the tensile strength, elongation at break and bending resistance of the ink. At the same time, the viscosity, thermal stability and glass transition temperature (Tg) of the system can also be improved. In addition, the auxiliary agent containing maleic anhydride can increase the thermal decomposition temperature of the light-curing ink and improve the thermal stability of the ink.
[0037] Specifically, the structure of the auxiliary agent may include at least one of the following formulas (a) to (g):
[0038]
[0039] In formula (c), formula (d) and formula (f), n is a positive integer of 1 to 10.
[0040] Preferably, an auxiliary agent containing two maleic anhydride structures is selected.
[0041] Further, the photocrosslinking initiator includes one or more of TPO, TEPO, 1173, 184, 819, 4-methoxybenzaldehyde, 4,4'-bis(dimethylamino)benzophenone, 4,4'-dichlorobenzophenone, 3,3'-dimethyl-2-methoxybenzophenone, hydroxybenzophenone, dibenzoylphenylphosphine oxide and benzoyldiphenylphosphine oxide.
[0042] It should be noted that the ultraviolet light curable monomer used in the present invention is a mixture of (meth) acrylate containing a long carbon chain and a bridge ring type photocurable monomer, wherein the (meth) acrylate containing a long carbon chain has a relatively strong intermolecular entanglement and interaction due to its long carbon chain structure, which will increase the viscosity of the ink, and the structural complexity of the bridge ring type photocurable monomer will also have a certain effect on the viscosity. The presence of the fluorinated aryl compound reduces the intermolecular interaction force, and to a certain extent can reduce the high viscosity effect brought by the (meth) acrylate containing a long carbon chain and the bridge ring type photocurable monomer. By adjusting the ratio of the three, the present invention can obtain a suitable viscosity range, which can not only ensure the fluidity of the ink during the printing process, but also prevent the occurrence of sagging. At the same time, the (meth) acrylate containing a long carbon chain usually has good flexibility, which can improve the elongation at break of the ink, the structural rigidity of the bridge ring type photocurable monomer may increase the tensile strength, and the presence of the fluorinated aryl compound will increase the intermolecular interaction force. Under the joint action of the three, the elongation at break and the tensile strength of the encapsulated ink are balanced by adjusting the ratio. Higher elongation at break can make the ink more tough and less likely to break when subjected to external forces; higher tensile strength can ensure the strength and stability of the ink during use. In addition, the addition of maleic anhydride structural additives can also reduce the amount of photocrosslinking initiator used, thereby reducing the cost of the ink. This is because there is a conjugated system in the maleic anhydride molecule, that is, the alternating single and double bond structure between the carbon-carbon double bond and the carbonyl group. This conjugated system can absorb ultraviolet light and undergo electronic transitions. This electronic transition requires ultraviolet light of a specific energy, and the ultraviolet light energy of 395nm wavelength matches the electronic structure of the maleic anhydride molecule. When 395nm ultraviolet light is irradiated on the maleic anhydride molecule, the energy will be absorbed and stimulate the electronic transition within the molecule. The electrons will transition from the lower energy level π bond orbital to the higher energy level π* antibonding orbital, resulting in light absorption of the molecule. That is, the maleic anhydride additive can synergize with the photocrosslinking initiator to enhance the activity of the photocrosslinking initiator. This means that under the same curing conditions, the same curing effect can be achieved using less photocrosslinking initiator.
[0043] After actual testing, the encapsulation composition formed by the present invention has a surface tension of 29 dyne / cm to 34 dyne / cm at a temperature of 25±5°C, a viscosity of 20 cps to 25 cps, is suitable for inkjet printing, and has a dielectric constant of only 2.5 to 2.6.
[0044] In a second aspect, the present invention provides a method for using the above encapsulation composition, the specific steps are as follows:
[0045] Step 1) firstly attaching the encapsulation composition to the surface of the electronic device to be encapsulated by spin coating, doctor blade coating, screen printing or inkjet printing;
[0046] Step 2) irradiating the encapsulation composition with ultraviolet light having a wavelength of 250 nm to 400 nm for 30 s to 600 s, and finally curing the composition to form an organic film having a thickness of 5 μm to 55 μm.
[0047] Wherein, in step 1), the encapsulation composition is attached to the surface of the electronic device to be encapsulated, specifically a substrate such as silicon nitride and ITO.
[0048] In a third aspect, the present invention also provides a use of the above-mentioned encapsulation composition in the preparation of an organic barrier film for waterproofing and oxygen-blocking electronic components, wherein the electronic components include other electronic devices such as organic light-emitting diodes, photosensors, or photovoltaic devices.
[0049] Compared with the prior art, the present invention has the following beneficial effects:
[0050] The encapsulation composition provided by the present invention is mainly composed of a fluorinated aromatic compound, an ultraviolet light curable monomer, an auxiliary agent and a photocrosslinking initiator in a specific ratio, has a viscosity between 20cps and 25cps, a surface tension between 29dyne / cm and 34dyne / cm, and has good printing performance. In the encapsulation composition, by introducing fluorinated aromatic compounds, the overall polarity of the ink can be changed to be closer to non-polarity, which can effectively reduce the dielectric properties of the encapsulation material; the mixture of (methyl) acrylates containing long carbon chains and bridge ring photocurable monomers is selected as the ultraviolet light curable monomer, which can effectively solve the cracking problem of the thick film and make it have excellent flexibility (appropriate tensile strength and elongation at break) and good thermal stability; in addition, by adding an auxiliary agent containing a maleic anhydride structure, the mechanical properties of the system can be improved, the tensile strength, elongation at break, and bending resistance of the ink can be improved, and the viscosity, thermal stability, glass transition temperature and thermal decomposition temperature of the system can also be improved, and the amount of photocrosslinking initiator can be reduced to save costs, so that the overall performance of the cured film layer is better, suitable for a variety of application scenarios and has a long service life. DETAILED DESCRIPTION
[0051] Here, exemplary embodiments will be described in detail, and the embodiments described in the following exemplary embodiments do not represent all embodiments consistent with the present invention. Instead, they are only examples consistent with some aspects of the present invention described in detail in the appended claims.
[0052] In order to enable those skilled in the art to better understand the technical solution of the present invention, the present invention is further described in detail below in conjunction with relevant experiments.
[0053] Preparation Example 1 (Synthesis of (R)-1-(3,5-bis(trifluoromethyl)phenyl)ethyl-2-(trifluoromethyl)acrylate represented by the following formula (1))
[0054]
[0055] The specific synthesis process is as follows:
[0056] 1) At 25 degrees Celsius and in a nitrogen atmosphere, 68.0 grams of oxalyl chloride were added dropwise to a solution containing 50.0 grams (386 millimoles) of trifluoromethylacrylic acid and 90 milliliters of dichloromethane, and finally a catalytic amount of N,N-dimethylformamide was added. The reaction mixture was heated to reflux at 50 degrees Celsius for 5 hours, and then the solvent and excess reagents were removed and concentrated using a rotary evaporator to obtain 2-trifluoromethylacryloyl chloride as a yellow liquid, which was directly used for the next step without purification.
[0057] 2) Add 122.0 g of (R)-1-(3,5-bis(trifluoromethyl)phenyl)ethanol (CAS: 127852-28-2) to a 1000 ml three-necked round-bottom flask equipped with a magnetic stirrer and a constant pressure dropping funnel, and use a double-row tube to perform vacuum and nitrogen filling operations three times. Under a nitrogen atmosphere, add 500 ml of anhydrous dichloromethane and 40.0 g, 38 ml of pyridine, and then cool the reaction system to 0°C. Take the 2-trifluoromethylacryloyl chloride obtained in the previous step and add it to the constant pressure dropping funnel. Slowly add the mixed solution to the 0°C reaction system at a rate of 1 drop / second, and stir vigorously to ensure that the acid chloride is dispersed in time and fully. After the dropwise addition is completed, the mixture is stirred at room temperature overnight to react. After the reaction, the solution was neutralized with dilute hydrochloric acid; then, the neutralized solution was washed with a saturated sodium bicarbonate solution of the aqueous phase; then, the organic phase was removed, and the aqueous phase was extracted with ethyl acetate; then, the organic solutions were combined and distilled for the first time to reduce the volume; finally, the remaining material was purified by silica gel column chromatography, and finally the purified product was distilled again to finally obtain 99.5 g of colorless liquid (R)-1-(3,5-bis(trifluoromethyl)phenyl)ethyl-2-(trifluoromethyl)acrylate with a yield of 83%.
[0058] Preparation Example 2 (Synthesis of 5-fluoronaphthalen-1-yl-2-(trifluoromethyl)acrylate represented by the following formula (7))
[0059]
[0060] The specific synthesis process is as follows:
[0061] 1) At 25 degrees Celsius and in a nitrogen atmosphere, 68.0 grams of oxalyl chloride were added dropwise to a solution containing 50.0 grams (386 millimoles) of trifluoromethylacrylic acid and 90 milliliters of dichloromethane, and finally a catalytic amount of N,N-dimethylformamide was added. The reaction mixture was heated to reflux at 50 degrees Celsius for 5 hours, and then the solvent and excess reagents were removed and concentrated using a rotary evaporator to obtain 2-trifluoromethylacryloyl chloride as a yellow liquid, which was directly used for the next step without purification.
[0062] 2) Add 45.0 g of 5-fluoronaphthalene-1-ol (CAS: 61761-32-8) to a 1000 ml three-necked round-bottom flask equipped with a magnetic stirrer and a constant pressure dropping funnel, and use a double-row tube to perform vacuum and nitrogen filling operations three times. Under a nitrogen atmosphere, add 500 ml of anhydrous dichloromethane and 27.0 g, 27.4 ml of pyridine, and then cool the reaction system to 0°C. Take the 2-trifluoromethylacryloyl chloride obtained in the previous step and add it to the constant pressure dropping funnel. Slowly add the mixed solution dropwise into the 0°C reaction system at a rate of 1 drop / second, and stir vigorously to ensure that the acyl chloride is promptly and fully dispersed. After the dropwise addition is completed, the mixture is stirred at room temperature overnight to react. After the reaction, the solution was neutralized with dilute hydrochloric acid; then, the neutralized solution was washed with a saturated sodium bicarbonate solution of the aqueous phase; then, the organic phase was removed, and the aqueous phase was extracted with ethyl acetate; then, the organic solutions were combined and distilled for the first time to reduce the volume; finally, the remaining material was purified by silica gel column chromatography, and the purified product was distilled again to finally obtain 70.5 g of colorless liquid 5-fluoronaphthalene-1-yl-2-(trifluoromethyl)acrylate with a yield of 89%.
[0063] Preparation Example 3 (Synthesis of perfluorobenzene 2-fluoroacrylate represented by the following formula (6))
[0064]
[0065] The specific synthesis process is as follows:
[0066] 1) At 0 degrees Celsius and in a nitrogen atmosphere, 105.7 grams of oxalyl chloride were added dropwise to a solution containing 50.0 grams (555 millimoles) of 2-fluoroacrylic acid and 90 milliliters of dichloromethane, and finally a catalytic amount of N,N-dimethylformamide was added. The reaction mixture was reacted at room temperature for 5 hours, and then the solvent and excess reagents were removed and concentrated using a rotary evaporator to obtain 2-fluoroacryloyl chloride as a yellow solid, which was directly used for the next step without purification.
[0067] 2) Add 65.0 g of perfluorobenzene-1-ol (CAS: 647-42-7) to a 1000 ml three-necked round-bottom flask equipped with a magnetic stirrer and a constant pressure dropping funnel, and use a double-row tube to perform vacuum and nitrogen filling operations three times. Under a nitrogen atmosphere, add 500 ml of anhydrous dichloromethane and 53.6 g, 54.6 ml of pyridine, and then cool the reaction system to 0°C. Take the 2-fluoroacryloyl chloride obtained in the previous step and add it to the constant pressure dropping funnel. Slowly add the mixed solution dropwise into the 0°C reaction system at a rate of 1 drop / second, and stir vigorously to ensure that the acid chloride is dispersed in time and fully. After the dropwise addition is completed, the mixture is stirred at room temperature overnight to react. After the reaction, the solution was neutralized with dilute hydrochloric acid; then, the neutralized solution was washed with a saturated sodium bicarbonate solution of the aqueous phase; then the organic phase was removed, and the aqueous phase was extracted with ethyl acetate; then, the organic solutions were combined and distilled for the first time to reduce the volume; finally, the remaining material was purified by silica gel column chromatography, and the purified product was distilled again to finally obtain 85.5 g of colorless liquid perfluorobenzene 2-fluoroacrylate with a yield of 94%.
[0068] The auxiliary agent used in Comparative Example 8 of the present invention is the formula (i) in the following formula (g) to formula (i):
[0069]
[0070] Example 1
[0071] The encapsulation composition provided in an embodiment of the present invention comprises, by weight, 35 parts of a fluorinated aromatic compound, 30 parts of an ultraviolet light-curable monomer, 5 parts of an auxiliary agent, and 3 parts of a photocrosslinking initiator; wherein the ultraviolet light-curable monomer is a mixture, comprising 20 parts of a (meth)acrylate containing a long carbon chain and 10 parts of a bridged ring photocurable monomer, and the auxiliary agent contains at least two maleic anhydride structures.
[0072] Specifically, the fluoroaryl compound is selected from the formula (1) synthesized by Preparation 1.
[0073] The (meth)acrylate containing a long carbon chain is selected from 1,6-hexanediol diacrylate.
[0074] The bridge ring photocurable monomer is isobornyl acrylate.
[0075] The auxiliary agent is selected from formula (e);
[0076] TPO was selected as the photocrosslinking initiator.
[0077] When preparing the encapsulation composition, 35 parts of formula (1), 20 parts of 1,6-hexanediol diacrylate, 10 parts of isobornyl acrylate, 5 parts of formula (e) and 3 parts of TPO are added to a stainless steel container bottle at room temperature and in a light-proof environment, and mixed and stirred until the initiator is completely dissolved. After standing, the target encapsulation composition is obtained.
[0078] Example 2
[0079] The encapsulation composition provided in an embodiment of the present invention comprises, by weight, 20 parts of a fluorinated aromatic compound, 40 parts of an ultraviolet light-curable monomer, 10 parts of an auxiliary agent, and 3 parts of a photocrosslinking initiator; wherein the ultraviolet light-curable monomer is a mixture, comprising 25 parts of a (meth)acrylate containing a long carbon chain and 15 parts of a bridged ring photocurable monomer, and the auxiliary agent contains at least two maleic anhydride structures.
[0080] Specifically, the fluoroaryl compound is selected from the formula (1) synthesized by Preparation 1.
[0081] The (meth)acrylate containing a long carbon chain is selected from 2-methyl-2-acrylic acid-1,9-nonanediol dimethacrylate.
[0082] The bridged ring photocurable monomer is dicyclopentane methacrylate.
[0083] The auxiliary agent is selected from formula (e);
[0084] TPO was selected as the photocrosslinking initiator.
[0085] When preparing the encapsulation composition, 20 parts of formula (1), 25 parts of 2-methyl-2-acrylic acid-1,9-nonanediol dimethacrylate, 15 parts of dicyclopentane methacrylate, 10 parts of formula (e) and 3 parts of TPO are added to a stainless steel container bottle at room temperature and in a light-proof environment, and mixed and stirred until the initiator is completely dissolved. After standing, the target encapsulation composition is obtained.
[0086] Example 3
[0087] The encapsulation composition provided in an embodiment of the present invention comprises, by weight, 20 parts of a fluorinated aromatic compound, 60 parts of an ultraviolet light-curable monomer, 15 parts of an auxiliary agent, and 2.5 parts of a photocrosslinking initiator; wherein the ultraviolet light-curable monomer is a mixture, comprising 30 parts of a (meth)acrylate containing a long carbon chain and 30 parts of a bridged ring photocurable monomer, and the auxiliary agent contains at least two maleic anhydride structures.
[0088] Specifically, the fluoroaryl compound is selected from the formula (7) synthesized in Preparation 2.
[0089] The (meth)acrylate containing a long carbon chain is selected from 1,12-dodecanediol di(meth)acrylate.
[0090] The bridged ring photocurable monomer is dicyclopentenyl acrylate.
[0091] The auxiliary agent is selected from formula (f);
[0092] The photocrosslinking initiator is hydroxybenzophenone.
[0093] When preparing the encapsulation composition, 20 parts of formula (7), 30 parts of 1,12-dodecanediol di(methyl)acrylate, 30 parts of dicyclopentenyl acrylate, 15 parts of formula (f) and 2.5 parts of hydroxybenzophenone are added to a stainless steel container bottle at room temperature and in a light-proof environment, and mixed and stirred until the initiator is completely dissolved. After standing, the target encapsulation composition is obtained.
[0094] Example 4
[0095] The encapsulation composition provided in an embodiment of the present invention comprises, by weight, 25 parts of a fluorinated aromatic compound, 65 parts of an ultraviolet light-curable monomer, 15 parts of an auxiliary agent, and 2.5 parts of a photocrosslinking initiator; wherein the ultraviolet light-curable monomer is a mixture, comprising 45 parts of a (meth)acrylate containing a long carbon chain and 20 parts of a bridged ring photocurable monomer, and the auxiliary agent contains at least two maleic anhydride structures.
[0096] Specifically, the fluoroaryl compound is selected from the formula (7) synthesized in Preparation 2.
[0097] The (meth)acrylate containing a long carbon chain is selected from 1,11-undecanediol dimethacrylate.
[0098] The bridged ring photocurable monomer is dicyclopentenyl acrylate.
[0099] The auxiliary agent is selected from formula (f);
[0100] The photocrosslinking initiator is hydroxybenzophenone.
[0101] When preparing the encapsulation composition, 25 parts of formula (7), 45 parts of 1,11-undecanediol dimethacrylate, 20 parts of dicyclopentenyl acrylate, 15 parts of formula (f) and 2.5 parts of hydroxybenzophenone are added to a stainless steel container bottle at room temperature and in a light-proof environment, mixed and stirred until the initiator is completely dissolved, and the target encapsulation composition is obtained after standing.
[0102] Example 5
[0103] The encapsulation composition provided in an embodiment of the present invention comprises, by weight, 22 parts of a fluorinated aromatic compound, 65 parts of an ultraviolet light-curable monomer, 20 parts of an auxiliary agent, and 2 parts of a photocrosslinking initiator; wherein the ultraviolet light-curable monomer is a mixture, comprising 35 parts of a (meth)acrylate containing a long carbon chain and 30 parts of a bridged ring photocurable monomer, and the auxiliary agent contains at least two maleic anhydride structures.
[0104] Specifically, the fluoroaryl compound is selected from the formula (6) synthesized by Preparation 3.
[0105] The (meth)acrylate containing a long carbon chain is selected from 1,5-pentanediol dimethacrylate.
[0106] The bridge ring photocurable monomer is cyclohexyl methacrylate.
[0107] The auxiliary agent is selected from formula (a);
[0108] The photo cross-linking initiator selected was 819.
[0109] When preparing the encapsulation composition, 22 parts of formula (6), 35 parts of 1,5-pentanediol dimethacrylate, 30 parts of cyclohexyl methacrylate, 20 parts of formula (a) and 2 parts of 819 are added to a stainless steel container bottle at room temperature and in a light-proof environment, and mixed and stirred until the initiator is completely dissolved. After standing, the target encapsulation composition is obtained.
[0110] Example 6
[0111] The encapsulation composition provided in an embodiment of the present invention comprises, by weight, 30 parts of a fluorinated aromatic compound, 48 parts of an ultraviolet light-curable monomer, 25 parts of an auxiliary agent, and 2 parts of a photocrosslinking initiator; wherein the ultraviolet light-curable monomer is a mixture, comprising 23 parts of a (meth)acrylate containing a long carbon chain and 25 parts of a bridged ring photocurable monomer, and the auxiliary agent contains at least two maleic anhydride structures.
[0112] Specifically, the fluoroaryl compound is selected from the formula (6) synthesized by Preparation 3.
[0113] The (meth)acrylate containing a long carbon chain is selected from 1,14-tetradecanediol di(meth)acrylate.
[0114] The bridge ring photocurable monomer is dicyclopentenyl ethoxylated acrylate.
[0115] The auxiliary agent is selected from formula (a);
[0116] The photo cross-linking initiator selected is 819.
[0117] When preparing the encapsulation composition, 30 parts of formula (6), 23 parts of 1,14-tetradecanediol di(methyl)acrylate, 25 parts of dicyclopentenyl ethoxylated acrylate, 25 parts of formula (a) and 2 parts of 819 are added to a stainless steel container bottle at room temperature and in a light-proof environment, and mixed and stirred until the initiator is completely dissolved. After standing, the target encapsulation composition is obtained.
[0118] Comparative Example 1
[0119] The only difference between this comparative example and Example 1 is that no fluorinated aromatic compound of any structure is added to the encapsulation composition of this comparative example.
[0120] Comparative Example 2
[0121] The only difference between this comparative example and Example 1 is that the amount of the compound of formula (1) added in this comparative example is 55 parts, that is, the amount of the fluorinated aromatic compound added in the encapsulation composition of this comparative example is too much.
[0122] Comparative Example 3
[0123] The only difference between this comparative example and Example 1 is that in this comparative example, 20 parts of butyl methacrylate and 10 parts of isobornyl acrylate are selected as the UV-curable monomers, that is, the encapsulation composition of this comparative example does not contain (meth)acrylate containing a long carbon chain.
[0124] Comparative Example 4
[0125] The only difference between this comparative example and Example 1 is that the UV-curable monomer in this comparative example is 20 parts of 1,6-hexanediol diacrylate and 10 parts of dodecafluoroheptyl methacrylate, that is, the encapsulation composition in this comparative example does not contain a bridged ring photocurable monomer.
[0126] Comparative Example 5
[0127] The only difference between this comparative example and Example 2 is that in this comparative example, 6 parts of 2-methyl-2-acrylic acid-1,9-nonanediol dimethacrylate and 30 parts of dicyclopentane methacrylate are selected as the ultraviolet light-curable monomer, that is, the mass ratio of the long carbon chain (meth)acrylate to the bridged ring photocurable monomer in the encapsulation composition of this comparative example is 6:30, which is not within the ratio range of (20-45): (10-30).
[0128] Comparative Example 6
[0129] The only difference between this comparative example and Example 1 is that no auxiliary agent is added to the encapsulation composition of this comparative example.
[0130] Comparative Example 7
[0131] The only difference between this comparative example and Example 1 is that the amount of the auxiliary agent added in the encapsulation composition of this comparative example is 30 parts of formula (e), that is, the amount of the auxiliary agent added in the encapsulation composition of this comparative example is too much.
[0132] Comparative Example 8
[0133] The only difference between this comparative example and Example 1 is that the amount of the auxiliary agent added to the encapsulation composition of this comparative example is 5 parts of formula (i), that is, the auxiliary agent added to the encapsulation composition of this comparative example does not contain at least two maleic anhydride structures.
[0134] Table 1 Raw material ratios of Examples 1 to 6 and Comparative Examples 1 to 8
[0135]
[0136] In order to verify the efficacy of the present invention, the applicant used the encapsulation compositions prepared in Examples 1 to 6 and Comparative Examples 1 to 8 and used a KM1024 inkjet print head / Unijet device to print on ITO at 30 mW / cm 2 The film was cured by irradiation with UV light for 600s, and a 30μm thick cured film was obtained for performance testing. The specific aspects include the following:
[0137] (1) Surface tension: The surface tension was tested using a surface tension meter (QBZY-2 surface tension meter). The test was conducted at 25°C. Defoaming centrifugation was performed before the test. Each sample was tested 5 times and the final data was averaged.
[0138] (2) Viscosity: The viscosity of the high-refractive precursor liquid was tested using a rotational rheometer (EVO type rotational viscometer). The test was carried out at 25°C. A 20 mm diameter conical rotor was used for the test. The shear rate was set at 0.01 s-1 to 500 s-1. The viscosity of the sample at a shear rate of 10 s-1 was selected for comparison. Each sample was tested 5 times and the final data was averaged.
[0139] (3) Refractive index: A pure organic inkjet printing high refractive index ink was printed on a glass substrate and subjected to UV curing by UV irradiation at 30 mW / cm2 in a nitrogen atmosphere to produce a cured film layer having a size of 5 mm×15 mm×0.1 mm (width×length×thickness), which was then tested using an Abbe refractometer.
[0140] (4) Light transmittance: Samples were prepared according to the method for forming a cured pattern except that no mask was used. The light transmittance of the cured film in the visible light range of 400 nm to 800 nm was measured using a UV-visible spectrophotometer (U-3900 Hitachi).
[0141] (5) Glass transition temperature (Tg): tested by differential scanning calorimetry (DSC), test conditions: test atmosphere N2 / O2; test temperature range: -180°C to 550°C; heating rate: 10°C / min.
[0142] (6) Photocuring rate: The encapsulation ink composition was inkjet printed on a glass substrate and subjected to UV curing for 120 s by UV irradiation at 30 mW / cm2 to produce a sample with a size of 3 cm×7.5 cm×18 μm (width×length×thickness), and then the absorption peak intensities of the encapsulation glue before curing and the film after curing near 1635 cm-1 (C=C) and 1720 cm-1 (C=O) were measured using FT-IR (Nicolet iS50, Thermo-Fisher).
[0143] Photocuring rate (%) = |1-(F / S)| × 100;
[0144] Wherein, F is the ratio of the absorption peak intensity of the cured film near 1635 cm-1 to the absorption peak intensity near 1720 cm-1; S is the ratio of the absorption peak intensity of the uncured ink near 1635 cm-1 to the absorption peak intensity near 1720 cm-1.
[0145] (7) Dielectric constant: The dielectric constant of the composition was tested at 10 GHz using GB / T 1693-2007.
[0146] (8) Elongation at break: Based on GB / T 1040-92 "General test methods for mechanical properties of plastics (tensile)"; test conditions: tensile speed 1 mm / min, at least 5 specimens per group, and the average value of the test results. The sample size is a dumbbell-shaped specimen with a gauge length of 50 mm and a thickness of 10 μm.
[0147] (9) Tensile strength: Pure organic inkjet printing high refractive index ink was printed on a glass substrate and subjected to UV curing by UV irradiation at 30 mW / cm2 in a nitrogen atmosphere to prepare a cured film, which was measured in accordance with GB / T 1040-92 "General Test Method for Mechanical Properties of Plastics (Tensile)". Instrument: WDW-5A microcomputer-controlled electronic universal testing machine; Test conditions: tensile speed of 1 mm / min, at least 5 samples per group, and the test results were averaged.
[0148] (10) Bending resistance: An organic film of 2 cm × 5 cm × 3 μm (width × length × thickness) was formed on the surface of the PI substrate. The sample was prepared according to the method of forming the curing pattern except that the mask was not used. The short sides of the sample were fixed with tape. The sample was installed in a tensionless U-shaped folding tester (instrument name DLDMLH-FS, manufactured by Yuasa System Co., Ltd.). The outer diameter (Φ) of the bending part of the tester was set to 4 mm and the radius (R) was set to 2 mm. The sample was folded in half and subjected to a 180° dynamic bending test 200,000 times. The <Evaluation Criteria> are as follows: If the bending part does not have cracks or fractures, it is evaluated as (○); if the bending part has cracks or fractures, it is evaluated as (×).
[0149] (11) Thermal decomposition temperature: Using a thermogravimetric analyzer (TGA) in a nitrogen environment, 10 mg of a sample was heated from 25°C to 150°C, and then the sample weight was measured by removing water by maintaining it at 150°C for 30 minutes. The temperature was then raised to 600°C at a heating rate of 10°C / min, and the temperature at which the sample weight decreased by 1% by weight was determined as Td1%. The higher the thermal decomposition temperature, the better the thermal stability of the material, and vice versa.
[0150] The final test results are shown in Table 2 below:
[0151] Table 2 Test results of Examples 1 to 6 and Comparative Examples 1 to 8
[0152]
[0153] It can be seen from the test results of Table 2 that the encapsulation composition formed by the specific proportion of fluorinated aromatic compounds, ultraviolet curable monomers, auxiliary agents and photocrosslinking initiators in Examples 1 to 6 of the present invention has a viscosity (20cps to 25cps) and a surface tension (29dyne / cm to 34dyne / cm) that are suitable for inkjet printing, and has the advantages of high curing rate, light transmittance and refractive index, and the dielectric constant is significantly reduced. At the same time, the addition of (methyl) acrylates containing long carbon chains and bridge-ring photocurable monomers and auxiliary agents containing maleic anhydride increases the crosslinking density and thus improves the heat resistance, and its Tg temperature is 95°C to 105°C and excellent flexibility (tensile strength is increased to 30Mpa, elongation at break is increased to 6%). In addition, it also has excellent bending resistance, and the thermal decomposition temperature is also increased.
[0154] However, the test results of comparative example 1 show that if the fluorinated aromatic compound is not added to the formula, the dielectric reduction effect cannot be achieved; the test results of comparative example 2 show that the amount of fluorinated aromatic compound added is too much, the sample tension and viscosity are too small to meet the printing requirements, and the transmittance and photocuring rate are reduced, and the glass transition temperature and tensile strength are also reduced; the test results of comparative example 3 show that the use of short-chain (meth) acrylates reduces the curing rate of the obtained organic barrier layer photocurable adhesive, the surface tension and viscosity are not within the appropriate range, and it is not suitable for inkjet printing, and the bending part has cracks or cracks; in comparative example 4, the bridged ring photocurable monomer uses methacrylic acid In Comparative Example 5, the mass ratio of the (meth)acrylate containing a long carbon chain to the bridged ring photocurable monomer is 1:5, which is not within the ratio range given in the present invention, and a printing ink with low dielectric properties cannot be obtained, and the bending resistance is poor and does not meet the requirements; in Comparative Example 6, no auxiliary agent is added, and Td1% is only 150°C; in Comparative Example 7, a large amount of auxiliary agent is added, which will lead to excessive viscosity and cannot be printed; in Comparative Example 8, when an auxiliary agent (i) containing only one maleic anhydride is added, Td1% is also relatively low (156°C), and the other properties are not good.
[0155] In summary, the encapsulation composition provided by the present invention has outstanding performance in various performance aspects, and its viscosity and surface tension are within the range suitable for inkjet printing, and the cured encapsulation film generated after UV curing has excellent comprehensive performance, such as showing low dielectric constant, high light transmittance and good mechanical properties. Among the various components of the encapsulation composition, the fluorine-containing curable monomer has significant advantages, its source is wide and low price, the configuration method is simple and easy, at the same time, the low dielectric constant UV curing glue configured shows the characteristics of fast curing speed in practical applications, the formed film has good light transmittance and low dielectric constant, and these characteristics are extremely beneficial to the implementation of encapsulation protection for electronic devices. In addition, the addition of an auxiliary agent containing two maleic anhydride structures plays at least the following two roles: first, it can replace part of the photoinitiator to a certain extent, thereby reducing the amount of photoinitiator used and reducing production costs; second, it can effectively improve the thermal stability of the ink, thereby enhancing the stability and durability of the material under high temperature environment, so that it can better meet the use requirements of electronic device packaging under different working conditions.
[0156] The above description is only a specific embodiment of the present invention, so that those skilled in the art can understand or implement the present invention. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein can be implemented in other embodiments without departing from the spirit or scope of the present invention.
[0157] It should be understood that the present invention is not limited to what has been described above and that various modifications and changes may be made without departing from its scope. The scope of the present invention is limited only by the appended claims.
Claims
1. A composition for encapsulation, characterized in that The encapsulation composition comprises the following raw materials in parts by weight: 5 to 50 parts of a fluorinated aromatic compound, 10 to 70 parts of an ultraviolet light curable monomer, 5 to 25 parts of an auxiliary agent and 2 to 4 parts of a photocrosslinking initiator.
2. The encapsulation composition according to claim 1, characterized in that The structure of the fluorinated aromatic compound is shown in the following general formula (1): Wherein, PAHs in the general formula (1) represents polycyclic aromatic hydrocarbons, which refers to substituted or unsubstituted aromatic hydrocarbons containing two or more benzene rings, and at least one group on each aromatic hydrocarbon is substituted by L or Z; the L and Z are each independently selected from any one of H, F, CFH2, CF2H, CF3, C1-C12 fatty chain alkyl, C1-C12 fluoroalkyl and the groups shown in the following general formula (2), and at least one group among L and Z is a fluorine-containing group, and the fluorine-containing group is any one of F, CFH2, CF2H, CF3, C1-C12 fluoroalkyl and the groups shown in the following general formula (2); In the general formula (1) and the general formula (2), X is independently selected from one of F and CF3, Y is selected from one of -ORO- and -NHRO-, and R in the -ORO- or -NHRO- is selected from one of C0-C12 substituted or unsubstituted aliphatic chain alkyl, C3-C6 substituted or unsubstituted aliphatic cycloalkyl, and C6-C30 substituted or unsubstituted aryl.
3. The encapsulation composition according to claim 2, characterized in that The structure of the fluorinated aromatic compound includes at least one of the following formulas (1) to (10):
4. The encapsulation composition according to claim 1, characterized in that The ultraviolet light curable monomer is a mixture of a (meth)acrylate containing a long carbon chain and a bridge-ring photocurable monomer, and the mass ratio of the (meth)acrylate containing a long carbon chain to the bridge-ring photocurable monomer is (20-45): (10-30).
5. The encapsulation composition according to claim 4, characterized in that The (meth)acrylate containing a long carbon chain includes one or more of 1,6-hexanediol diacrylate, 2-methyl-2-acrylic acid-1,10-decanediol, 2-methyl-2-acrylic acid-1,9-nonanediol dimethacrylate, 1,5-pentanediol dimethacrylate, 1,11-undecanediol dimethacrylate, 1,12-dodecanediol di(meth)acrylate, 1,13-tridecanediol dimethacrylate, 1,14-tetradecanediol di(meth)acrylate or 1,18-octadecanediyl dimethacrylate; The bridged ring photocurable monomers include bridged ring diacrylate monomers containing six to twenty-five carbon atoms.
6. The encapsulation composition according to claim 1, characterized in that The auxiliary agent contains at least two maleic anhydride structures.
7. The encapsulation composition according to claim 6, characterized in that The structure of the auxiliary agent includes at least one of the following formulas (a) to (g): In formula (c), formula (d) and formula (f), n is a positive integer of 1 to 10.
8. The encapsulation composition according to claim 1, characterized in that The photocrosslinking initiator includes one or more of TPO, TEPO, 1173, 184, 819, 4-methoxybenzaldehyde, 4,4'-bis(dimethylamino)benzophenone, 4,4'-dichlorobenzophenone, 3,3'-dimethyl-2-methoxybenzophenone, hydroxybenzophenone, bisbenzoylphenylphosphine oxide or benzoyldiphenylphosphine oxide.
9. A method for using the encapsulation composition according to any one of claims 1 to 8, characterized in that: The specific steps include: Step 1) firstly attaching the encapsulation composition to the surface of the electronic device to be encapsulated by spin coating, doctor blade coating, screen printing or inkjet printing; Step 2: irradiate the encapsulation composition with ultraviolet light having a wavelength of 250 nm to 400 nm for 30 s to 600 s, and finally cure it to form an organic film of 5 μm to 55 μm.
10. Use of the encapsulation composition according to any one of claims 1 to 8 in preparing an organic barrier film for waterproofing and oxygen-blocking electronic components.
Citation Information
Patent Citations
Ink compositions, packaging structures, and semiconductor devices
CN115109464B